Breast cancer patient pathways to treatment in Turkey’s internal healthcare market :|a qualitative study - Kesici, Zeynep. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
The importance of managing noncommunicable diseases, such as cancer, has been viewed as a vital component of Universal Health Coverage (UHC) due to their worldwide high prevalence, significant disease burden, and sometimes life-long medical ramifications for patients. Having been deemed an achiever of UHC, Turkey has implemented an internal market for healthcare to achieve equal access to healthcare. Against this background, this thesis explores breast cancer patients’ experiences of access and pathways to treatment in private hospitals offering publicly-funded services (PHOPS) in Turkey. It examines the factors that shape these pathways and the implications of these pathways for patients. This thesis relies on a thematic analysis of an exploratory qualitative study that includes 12 semi-structured in-depth interviews conducted between July and August 2021 with female breast cancer patients using private hospitals. It reveals two interrelated factors that shape patient pathways during the diagnosis and treatment stages: the projected cost of treatment and barriers to accessing integrated medical care. Based on these two factors, two distinct patient pathways, insured and underinsured patient pathways, are identified. While patients with private health insurance alongside compulsory general health insurance experience easy access to timely and effective treatment (insured pathway), those who only count on the latter deal with complicated processes of accessing treatment such as combining different providers (underinsured pathway). The thesis concludes that the insurance status of patients has a significant influence on experiences of access and pathways to treatment in PHOPS.
Keywords: Health -- Turkey.; Breast -- Cancer.